EFEKTIFITAS FILTER BAHAN ALAMI DALAM PERBAIKAN KUALITAS AIR MASYARAKAT NELAYAN WILAYAH PESISIR KABUPATEN BANGK - Adi, Wahyu; Sari, Suci Puspita; ST, Umroh (Universitas Bangka Belitung, 2014)
Local fisherman communities in Bangka regency coastal, have a clean water supply problem. They Local fisherman communities in Bangka regency coastal, have a clean water supply problem. They have to buy clean water for 2.000 IDR per 20 liters. This research about water filter effectiveness, using natural resources. Research on the effectiveness of the filter with natural materials need to be done to overcome these problems . With the experimental method, stacking filters designed with several treatment sequence. Treatment 1: rubble, fibers, quartz sand, charcoal, cotton. Treatment 2: Fine sand, gravel, palm, coconut shell charcoal, and rubble. Treatment 3: rubble, gravel, fibers, fine sand, charcoal, cotton. Of the three treatment showed no clean water quality standard approach , and among the three, treatment 2 were approaching the value of clean water quality standard.